Ultraviolet photoelectric detector based on ZnMgO ferroelectric regulation and control
By using ZnMgO ferroelectric material as the photosensitive layer and the ferroelectric regulation layer in the ultraviolet photodetector to adjust the ferroelectrode polarization state, the problems of low quantum efficiency and low sensitivity in the deep ultraviolet band are solved, and the further development of the existing detectors is achieved. High responsiveness and environmental stability.
Patent Information
- Application Number
- CN202411639700.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
AI Technical Summary
The existing ultraviolet photodetectors have low quantum efficiency and low sensitivity in the deep ultraviolet band, which limits their development, and the traditional ferroelectric-controlled photodetectors have low responsiveness.
ZnMgO ferroelectric material is used as the photosensitive layer and the ferroelectric regulation layer. The ferroelectroelectric polarization state is adjusted by adjusting the Mg content and the applied electric field, thereby improving the responsiveness and signal response of the detector.
It significantly improves the sensitivity and response speed of the ultraviolet photodetector, enhances the photoelectric conversion efficiency, and has better environmental stability and anti-interference ability.
Smart Images

Figure CN119451246A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor photoelectric detectors, and in particular to an ultraviolet photoelectric detector based on ZnMgO ferroelectric regulation. Background Art
[0002] Ultraviolet light refers to electromagnetic radiation with a wavelength of 10 nm-400nm. Ultraviolet light (UV) on the earth mainly comes from the sun. Although ultraviolet radiation accounts for only a small part (~7%) of the total solar radiation in the solar radiation spectrum at the top of the atmosphere and at sea level, it has a great impact on the biosphere. It can be classified more finely according to the characteristics of each band. Vacuum ultraviolet (VUV) (10-200nm), VUV will be strongly absorbed by oxygen in the air and can only propagate in the air, hence the name. It has many applications in sterilization, pollution treatment, surface modification, etc. Ultraviolet C (UVC) (200-280nm), also known as short-wave sterilization ultraviolet. It has the weakest penetration ability and cannot penetrate most transparent materials such as glass and plastic. The ultraviolet radiation in this band of sunlight is strongly absorbed and scattered by oxygen, nitrogen and ozone molecules in the atmosphere, and it can hardly reach the surface of the earth. Therefore, this band is also called solar blind ultraviolet. Since the ultraviolet content in this band in the near-ground atmosphere is very small, it has very weak interference when used for missile or aircraft early warning. It is very harmful to the human body. Short-term exposure can burn the skin, and long-term or high-intensity exposure can also cause skin cancer. At the same time, this characteristic can also be used for sterilization and disinfection. Ultraviolet B (UVB) (280-320nm) The shorter wavelength part will be absorbed by transparent glass. Most of the medium-wave ultraviolet rays contained in sunlight are absorbed by the ozone layer. In the afternoon of summer, it will be particularly strong and have an erythema effect on the human body. It can promote the metabolism of minerals in the body, but long-term or excessive exposure will cause the skin to tan and cause redness, swelling and peeling. Ultraviolet A (UVA) (320-400nm) It has strong penetrating power. More than 98% of the long-wave ultraviolet rays contained in sunlight can penetrate the ozone layer and clouds to reach the earth's surface. UVA can directly reach the dermis of the skin, destroy elastic fibers and collagen fibers, and make the skin darker. Because of the huge impact of UVA and UVB on human health, ultraviolet detection in this band is of great significance in environmental monitoring.
[0003] The traditional ones are mainly photomultiplier tubes and silicon-based photodiodes. Although photomultiplier tubes have high gain and high sensitivity, their development is limited by a series of problems such as large size, high power consumption, susceptibility to magnetic field interference, limited sensitivity, and high cost. Silicon-based photodiodes have low quantum efficiency and relatively low sensitivity in the deep ultraviolet band, which also limits their development. In recent years, wide-bandgap semiconductor ultraviolet detectors have the advantages of light weight, small size, no need for filters, and low cost, and are expected to replace vacuum photomultiplier tubes and Si-based photomultiplier tubes to become the third generation of ultraviolet detectors.
[0004] The reserve of Zn in ZnO-based materials is high. By adjusting the content of Mg doped, the band gap width can be controlled between 3.3-7.8eV, and the preparation temperature of ZnMgO alloy is relatively low. Ferroelectric materials refer to materials with spontaneous polarization, and the direction of spontaneous polarization can change with the applied electric field. Magnesium zinc oxide (MgZnO) is a newly discovered ferroelectric oxide with wurtzite structure. It has a standard hysteresis loop, large residual polarization field, low coercive field, high Curie temperature, adjustable band gap of 3.3~7.8eV, abundant raw materials, green and environmentally friendly, and low growth temperature. Therefore, MgZnO is one of the ideal materials for preparing ferroelectric photodetectors.
[0005] Currently, there is no report on the research of ZnMgO ferroelectrically controlled ultraviolet photodetectors in the prior art. In the past, ferroelectrically controlled photodetector materials such as BaTiO3 and PZLT had low photoelectric properties, which led to low photodetector responsivity (10 -5 -10 -8 A / W), and ZnMgO as a new type of ferroelectric material not only has excellent photoelectric properties but also has excellent ferroelectric properties. Using its own ferroelectric effect to regulate the performance of photodetectors can increase the responsiveness of the detector by 3-5 orders of magnitude. Summary of the invention
[0006] In order to solve the above problems, the present invention provides an ultraviolet photoelectric detector based on ZnMgO ferroelectric regulation.
[0007] The present invention aims to provide an ultraviolet photodetector based on ZnMgO ferroelectric regulation, comprising: a substrate, a conductive layer, a ZnMgO ferroelectric regulation layer and a Schottky contact electrode which are stacked closely from bottom to top; The content of Mg component in the ZnMgO ferroelectric control layer is 10-55%; The Schottky contact electrode adopts a spider web structure, in which a portion of the annular region of the spider web structure is light-transmissive and another portion is light-impermeable, and is used to effectively collect carriers.
[0008] Preferably, the ZnMgO ferroelectric control layer serves as the ferroelectric control layer and the photosensitive layer, and has a thickness of 50-200 nm.
[0009] Preferably, the Schottky contact electrode is made of Pt and has a thickness of 10-200 nm.
[0010] Preferably, the conductive layer is made of Pt and has a thickness of 50-300 nm.
[0011] Preferably, the thickness of the conductive layer is 50-200 nm.
[0012] Preferably, the substrate is c-plane sapphire.
[0013] Preferably, it is prepared by the following method: S1. Clean the substrate and blow dry; S2. Place the substrate into a vacuum chamber, fix the target material so that the target material and the substrate are kept at a distance of 30 to 60 cm, and deposit a conductive layer on the substrate; S3. Prepare a ZnMgO ferroelectric control layer on the surface of the conductive layer using plasma-assisted molecular beam epitaxy technology; S4. Photolithography and development are performed on the surface of the ZnMgO ferroelectric control layer to prepare a pattern of a Schottky contact electrode; S5. Use magnetron sputtering to deposit metal on the surface of the ZnMgO ferroelectric control layer, and then peel it off to obtain a Schottky contact electrode, thereby completing the preparation of an ultraviolet photodetector based on ZnMgO ferroelectric control.
[0014] Preferably, step S3 specifically includes the following sub-steps: S301. Place the sample prepared in step S2 with the conductive layer facing upward into the injection chamber, and place it into the growth chamber after evacuation; S302. The temperature is raised to 640-660°C for pretreatment; after the pretreatment, liquid nitrogen is introduced, the temperature is adjusted to 350-450°C, and the growth is carried out for 2-4 hours under the conditions of oxygen source flow rate 2-3sccm, RF power 150-250W, zinc source temperature 220-230°C, and magnesium source temperature 225-235°C; S303. After the growth is completed, turn off the RF, turn off the oxygen source, lower the temperature of the substrate, zinc source and magnesium source to 75~85℃, take out the sample, and complete the preparation of the ZnMgO ferroelectric control layer.
[0015] Preferably, in step S302, the oxygen source flow rate is 2.2 sccm, the RF power is 200 W, the zinc source temperature is 225° C., and the magnesium source temperature is 230° C.
[0016] Preferably, step S5 specifically includes the following sub-steps: S501. Place the photolithographic sample into a magnetron sputtering vacuum chamber, fix the target, evacuate the chamber, introduce argon gas, and perform metal deposition at a radio frequency power of 130-200 W after stabilization; S502. After the deposition is completed, the RF is turned off, the argon flow is turned off, the molecular pump is turned off, the gas is inflated and the sample is taken out; after the sample is taken out, ultrasonic peeling is performed in acetone; S503. Removing part of the ZnMgO ferroelectric control layer by wet etching to expose the conductive layer; S504. The sample is spin-coated with a positive photoresist using a coating machine, photolithography, development, washing in deionized water, and then dried with nitrogen; S505. Place the photolithographic sample in dilute hydrochloric acid for etching for 1-3 seconds, wash with deionized water for 1 minute, and blow dry with nitrogen; perform ultrasonic peeling in acetone to obtain a Schottky contact electrode to complete the preparation.
[0017] Compared with the prior art, the present invention can achieve the following beneficial effects: The biggest difference between the present invention and the existing ferroelectric control type photodetector is the improvement in materials. The new ferroelectric ZnMgO replaces the traditional ferroelectric material and uses the ferroelectric effect to improve the performance of the device. In the ultraviolet photodetector with ZnMgO ferroelectric control of the present invention, the MgZnO layer is both a photosensitive layer and a ferroelectric control layer. As a ferroelectric control layer, the electric polarization state of the film can be adjusted under the action of an external electric field, which is conducive to improving the sensitivity and signal response of the detector. At the same time, because the MgZnO ferroelectric film layer has a high dielectric constant, the dark current of the detector can be reduced, the noise can be reduced, and the signal-to-noise ratio can be improved. By adjusting the polarization state of the ferroelectric MgZnO layer by an external electric field, the performance of the detector can be dynamically adjusted, and it is suitable for different working conditions or light source characteristics. The MgZnO ferroelectric film layer has non-volatility and high resistance characteristics, which makes the detector have the advantage of low power consumption when working. In summary, the detector of the present invention realizes ferroelectric control, improves the photoelectric conversion efficiency of the detector, significantly improves the sensitivity and response speed of the detector, and has better environmental stability. In addition, the present invention also has the advantages of wide spectrum response, strong anti-interference ability, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic structural diagram of an ultraviolet photodetector based on ZnMgO ferroelectric regulation provided according to an embodiment of the present invention.
[0019] Figure 2 It is a schematic diagram of a Schottky spiderweb electrode structure of an ultraviolet photodetector based on ZnMgO ferroelectric regulation provided according to an embodiment of the present invention.
[0020] Figure 3 This is an XRD diagram of the conductive layer of the ultraviolet photodetector based on ZnMgO ferroelectric regulation provided according to an embodiment of the present invention.
[0021] Figure 4This is an XRD diagram of a ZnMgO ferroelectric control layer of an ultraviolet photodetector based on ZnMgO ferroelectric control provided according to an embodiment of the present invention.
[0022] Reference numerals: 1. Substrate; 2. Conductive layer; 3. ZnMgO ferroelectric control layer; 4. Schottky contact electrode. DETAILED DESCRIPTION
[0023] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In the following description, the same modules are represented by the same reference numerals. In the case of the same reference numerals, their names and functions are also the same. Therefore, the detailed description thereof will not be repeated.
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not constitute a limitation of the present invention.
[0025] like Figure 1-Figure 2 As shown, the present invention provides an ultraviolet photodetector based on ZnMgO ferroelectric regulation, comprising: a substrate 1, a conductive layer 2, a ZnMgO ferroelectric regulation layer 3 and a Schottky contact electrode 4 which are stacked closely from bottom to top; The content of Mg component in the ZnMgO ferroelectric control layer 2 is 10-55%, and it has a hexagonal wurtzite crystal structure; The Schottky contact electrode 4 adopts a spider web structure ( Figure 2 ), a portion of the annular region of the spider-web structure is light-transmissive and another portion is opaque, which is used to effectively collect carriers.
[0026] Specifically, the substrate 1 is c-plane sapphire.
[0027] Specifically, the conductive layer 2 is made of Pt and has a thickness of 50-300 nm; preferably, the thickness is 50-200 nm.
[0028] Specifically, the ZnMgO ferroelectric control layer 3 has a thickness of 50-200 nm and covers a portion of the conductive layer.
[0029] Specifically, the material of the Schottky contact electrode 4 is Pt, and the thickness is 10~200nm. In the present application, the surface of the ZnMgO ferroelectric control layer has a Schottky contact electrode, which can establish a space charge region in the surface area, and work together with the spontaneous polarization inside the ZnMgO to realize the collection of carriers. The Schottky contact electrode is selected from the Pt electrode in the present application. Because it is opaque, a spider web structure is adopted, and the annular area is partially transparent and partially opaque, which can effectively collect carriers.
[0030] The preparation method is as follows: S1. Clean the substrate and blow dry; use ultrasonic cleaning such as acetone, ethanol, deionized water, etc. to clean, and blow dry with nitrogen after each cleaning; S2. Place the substrate into a vacuum chamber, fix the target material so that the target material and the substrate are kept at 30~60cm, and deposit a conductive layer on the substrate; specifically, a Pt thin film is prepared on the substrate as a conductive layer by a magnetron sputtering method, and high-purity argon gas is introduced during the reaction process, with a flow rate of 10~50sccm, a power of 50~200W, a growth temperature of 20~200℃, and a deposition time of 10~50min.
[0031] S3. Prepare a ZnMgO ferroelectric control layer on the surface of the conductive layer using plasma-assisted molecular beam epitaxy technology; S4. Photolithography and development are performed on the surface of the ZnMgO ferroelectric control layer to prepare a pattern of a Schottky contact electrode; S5. Use magnetron sputtering to deposit metal on the surface of the ZnMgO ferroelectric control layer, and then peel it off to obtain a Schottky contact electrode, thereby completing the preparation of an ultraviolet photodetector based on ZnMgO ferroelectric control.
[0032] Example 1 A method for preparing an ultraviolet photodetector based on ZnMgO ferroelectric regulation specifically comprises the following steps: S1. Ultrasonic clean the c-plane sapphire substrate with acetone, ethanol, and deionized water for 3 minutes respectively, and blow dry with nitrogen gas in each step.
[0033] S2. Place the c-plane sapphire substrate into a vacuum chamber and fix the Pt target. The distance between the Pt target and the sample to be deposited (substrate) is about 40 cm. Use magnetron sputtering to prepare a 100 nm thick Pt film as a conductive layer on the c-plane sapphire substrate. During the reaction, high-purity argon gas is introduced with a flow rate of 10~50sccm, a power of 50~200W, a growth temperature of 20~200℃, and a deposition time of 10~50min.
[0034] S3. Prepare a ZnMgO ferroelectric control layer on the surface of the conductive layer using plasma-assisted molecular beam epitaxy technology; the specific steps are as follows: S301. Place the sample prepared in step S2 into the injection chamber with the conductive layer facing upwards, first use a mechanical pump as a pre-pump for ten minutes, then turn on the molecular pump for 2 hours, shake open the valve and place the tray on the trolley, place the tray into the growth chamber through the trolley, and close the valve; S302. The support temperature was raised to 650°C and pretreated for two hours; after the pretreatment, liquid nitrogen was passed, the substrate temperature was 400°C during growth, the oxygen source flow rate was 2.2sccm, the RF power was 200W, the zinc source was 225°C, the magnesium source was 230°C, and the growth was three hours; S303. After the growth is completed, turn off the RF, turn off the oxygen source, lower the temperature of the substrate, zinc source (pure chemical element Zn placed in a crucible), and magnesium source (pure chemical element Zn placed in a crucible) to 80°C, take out the sample, and complete the preparation of the ZnMgO ferroelectric control layer.
[0035] S4. Photolithography and development are performed on the surface of the ZnMgO ferroelectric control layer to prepare a mask pattern of a Schottky contact electrode; the specific steps are as follows: S401. Spin-coat the negative photoresist on the sample prepared in step S3, and use the coating machine at 1000 rpm (pre-rotation) for 10s and 6000 rpm (actual rotation) for 20s; the photolithography target adopts a spider web structure, and the exposure is 30s. After the exposure is completed, bake it at 90°C for 6 minutes with a heating plate to solidify the photoresist; S402. Develop in a developer for 8-15 seconds. Immediately wash with deionized water and dry with nitrogen. Photolithography is completed to obtain a pattern of Schottky contact electrodes.
[0036] S5. Deposit metal on the surface of the ZnMgO ferroelectric control layer by magnetron sputtering, and then peel off to obtain a Schottky contact electrode; the specific steps are as follows: S501. Place the photolithographic sample into a magnetron sputtering vacuum chamber, fix the Pt target, and set the growth temperature to room temperature; evacuate the chamber to a certain vacuum degree, introduce Ar gas at a flow rate of 25 sccm, set the RF power to 150W after stabilization, and set the deposition time to 30 minutes; before deposition, pre-sputter for 20 minutes to remove impurities on the Pt surface; S502. After the deposition is completed, turn off the radio frequency, turn off the Ar gas flow, and turn off the molecular pump after the rotation speed drops below 100 rpm, inflate, and take out the sample; after taking out the sample, ultrasonically peel it in acetone for 3 minutes; S503. Removing part of the ZnMgO ferroelectric control layer by wet etching to expose the Pt conductive layer; S504. The sample was pre-spun at 1000 rpm for 10 s and then at 6000 rpm for 20 s using a coating machine, positive photoresist was spin-coated, baked on a 90°C hot plate for 6 min, exposed with a photolithography machine for 35 s, directly developed in a developer for 12 s, rinsed in deionized water for 2 min, and dried with nitrogen; S505. Take an appropriate amount of concentrated hydrochloric acid and prepare dilute hydrochloric acid in a volume ratio of 1:5, place the photolithographic sample into the dilute hydrochloric acid for corrosion for 2 seconds, wash it in deionized water for 1 minute, and blow it dry with nitrogen; then ultrasonically peel it in acetone for 3 minutes to obtain a Schottky contact electrode, and complete the device preparation. Figure 2 The spider web structure of the Schottky contact electrode is shown, the white area is the opaque area of the Pt electrode, and the black area is the translucent area.
[0037] The prepared conductive layer and ZnMgO ferroelectric control layer were characterized, and the results were as follows: Figure 3 and Figure 4 shown. Figure 3 The XRD pattern of the conductive layer (bottom electrode Pt) prepared on the c-plane sapphire substrate shows that 41.68° is the diffraction peak of c-plane sapphire 0006, and 39.76° is the diffraction peak of Pt electrode 111. Figure 4 The XRD diagram of the ferroelectric control layer ZnMgO prepared on the bottom electrode Pt shows that 41.68° is the diffraction peak of c-plane sapphire 0006, 39.76° is the diffraction peak of the Pt substrate 111, and 34.9° is the diffraction peak of the ZnMgO ferroelectric control layer 002. Judging from the peak intensity, the crystal quality of the thin film prepared by this method is very good.
[0038] Brief description of the principle of the present invention: The ZnMgO ferroelectrically controlled ultraviolet photodetector of the present invention is a ferroelectric material based on ZnMgO hexagonal wurtzite. Ferroelectric materials refer to materials that have spontaneous polarization and whose spontaneous polarization changes with the direction of the applied electric field. The working principle of the device is that when ultraviolet light with photon energy greater than the bandgap width of ZnMgO irradiates the device, electron-hole pairs are generated inside ZnMgO after passing through the spider web-shaped electrode; when an appropriate bias is applied to ZnMgO, ZnMgO will generate a spontaneous polarization field inside the entire film. When the direction of the spontaneous polarization is consistent with the direction of the built-in electric field of the device, it is conducive to the transmission of photogenerated carriers and can enhance the detection capability of the detector. When the direction of the spontaneous polarization of ZnMgO is opposite to the direction of the built-in electric field of the device, it is not conducive to the transmission of photogenerated carriers and can weaken the detection capability of the detector.
[0039] The built-in electric field of traditional detectors only exists at the interface. For ferroelectric materials, the ferroelectric polarization field exists in the entire ferroelectric material, and the direction of the ferroelectric polarization field can change with the change of the external bias direction, thus greatly improving the detection efficiency of carrier collection. This detector uses the spontaneous polarization field of ferroelectrics to control photoelectricity, greatly improving the detection performance of the detector.
[0040] The advantages of the present invention are: through the ferroelectric regulation of the ZnMgO film itself, the ultraviolet photodetector of the present invention realizes ferroelectric regulation, improves the photoelectric conversion efficiency of the detector, significantly improves the sensitivity and response speed of the detector, and has better environmental stability.
[0041] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps described in the disclosure of the present invention can be performed in parallel, sequentially or in different orders, as long as the desired results of the technical solution disclosed in the present invention can be achieved, and this document does not limit this.
[0042] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A UV photodetector based on ZnMgO ferroelectric regulation, characterized in that: include: A substrate, a conductive layer, a ZnMgO ferroelectric control layer and a Schottky contact electrode are tightly stacked from bottom to top; The content of Mg component in the ZnMgO ferroelectric control layer is 10-55%; The Schottky contact electrode adopts a spider web structure, in which a portion of the annular region of the spider web structure is light-transmissive and another portion is light-impermeable, and is used to effectively collect carriers.
2. The ultraviolet photodetector based on ZnMgO ferroelectric regulation according to claim 1, characterized in that: The ZnMgO ferroelectric control layer serves as a ferroelectric control layer and a photosensitive layer, and has a thickness of 50-200 nm.
3. The ultraviolet photodetector based on ZnMgO ferroelectric regulation according to claim 1, characterized in that: The Schottky contact electrode is made of Pt and has a thickness of 10-200 nm.
4. The ultraviolet photodetector based on ZnMgO ferroelectric regulation according to claim 1, characterized in that: The conductive layer is made of Pt and has a thickness of 50-300 nm.
5. The ultraviolet photodetector based on ZnMgO ferroelectric regulation according to claim 4, characterized in that: The thickness of the conductive layer is 50-200 nm.
6. The ultraviolet photodetector based on ZnMgO ferroelectric regulation according to claim 5, characterized in that: The substrate is c-plane sapphire.
7. A UV photodetector based on ZnMgO ferroelectric regulation according to any one of claims 1 to 6, characterized in that: Prepared by the following method: S1. Clean the substrate and blow dry; S2. Place the substrate into a vacuum chamber, fix the target material so that the target material and the substrate are kept at a distance of 30 to 60 cm, and deposit a conductive layer on the substrate; S3. Prepare a ZnMgO ferroelectric control layer on the surface of the conductive layer using plasma-assisted molecular beam epitaxy technology; S4. Photolithography and development are performed on the surface of the ZnMgO ferroelectric control layer to prepare a pattern of a Schottky contact electrode; S5. Use magnetron sputtering to deposit metal on the surface of the ZnMgO ferroelectric control layer, and then peel it off to obtain a Schottky contact electrode, thereby completing the preparation of an ultraviolet photodetector based on ZnMgO ferroelectric control.
8. The ultraviolet photodetector based on ZnMgO ferroelectric regulation according to claim 7, characterized in that: The step S3 specifically includes the following sub-steps: S301. Place the sample prepared in step S2 with the conductive layer facing upward into the injection chamber, and place it into the growth chamber after evacuation; S302. The temperature is raised to 640-660°C for pretreatment; after the pretreatment, liquid nitrogen is introduced, the temperature is adjusted to 350-450°C, and the growth is carried out for 2-4 hours under the conditions of oxygen source flow rate 2-3sccm, RF power 150-250W, zinc source temperature 220-230°C, and magnesium source temperature 225-235°C; S303. After the growth is completed, turn off the RF, turn off the oxygen source, lower the temperature of the substrate, zinc source and magnesium source to 75~85℃, take out the sample, and complete the preparation of the ZnMgO ferroelectric control layer.
9. The ultraviolet photodetector based on ZnMgO ferroelectric regulation according to claim 8, characterized in that: In step S302, the oxygen source flow rate is 2.2 sccm, the RF power is 200 W, the zinc source temperature is 225° C., and the magnesium source temperature is 230° C.
10. The ultraviolet photodetector based on ZnMgO ferroelectric control according to claim 7, characterized in that: The step S5 specifically includes the following sub-steps: S501. Place the photolithographic sample into a magnetron sputtering vacuum chamber, fix the target, evacuate the chamber, introduce argon gas, and perform metal deposition at a radio frequency power of 130-200 W after stabilization; S502. After the deposition is completed, the RF is turned off, the argon flow is turned off, the molecular pump is turned off, the gas is inflated and the sample is taken out; after the sample is taken out, ultrasonic peeling is performed in acetone; S503. Removing part of the ZnMgO ferroelectric control layer by wet etching to expose the conductive layer; S504. The sample is spin-coated with a positive photoresist using a coating machine, photolithography, development, washing in deionized water, and then dried with nitrogen; S505. Place the photolithographic sample in dilute hydrochloric acid for etching for 1-3 seconds, wash with deionized water for 1 minute, and blow dry with nitrogen; perform ultrasonic peeling in acetone to obtain a Schottky contact electrode to complete the preparation.